2016
DOI: 10.1007/s10916-016-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Acute Coronary Syndrome with a Support Vector Machine

Abstract: Acute coronary syndrome (ACS) is a serious condition arising from an imbalance of supply and demand to meet myocardium's metabolic needs. Patients typically present with retrosternal chest pain radiating to neck and left arm. Electrocardiography (ECG) and laboratory tests are used indiagnosis. However in emergency departments, there are some difficulties for physicians to decide whether hospitalizing, following up or discharging the patient. The aim of the study is to diagnose ACS and helping the physician wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 18 publications
1
36
0
1
Order By: Relevance
“…In the first experiment, we used the order of variables given by the MIFS-U filter to compare the capability of ν-SVM and feed-forward ANN models to predict the risk of death (as high or low) in patients admitted with ACS. In line with previous studies (Berikol et al, 2016;Kumari & Godara, 2011;Xing et al, 2007), the results indicated that the ν-SVM model is superior. However, the classifier biases did not diverge in terms of variable selection since both classifiers identified the same optimal subset of input variables: Age, Any Previous Revascularization, and Creatinine.…”
Section: Resultssupporting
confidence: 91%
“…In the first experiment, we used the order of variables given by the MIFS-U filter to compare the capability of ν-SVM and feed-forward ANN models to predict the risk of death (as high or low) in patients admitted with ACS. In line with previous studies (Berikol et al, 2016;Kumari & Godara, 2011;Xing et al, 2007), the results indicated that the ν-SVM model is superior. However, the classifier biases did not diverge in terms of variable selection since both classifiers identified the same optimal subset of input variables: Age, Any Previous Revascularization, and Creatinine.…”
Section: Resultssupporting
confidence: 91%
“…Support vector machine (SVM) classifiers are gaining significance as a robust classification tool in cancer genomics (13) and have been used for the diagnosis of various diseases, including chronic kidney disease (14) and acute coronary syndrome (15). In the present study, it was hypothesized that an SVM classifier based on optimal feature genes of PSS could facilitate the diagnosis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of this study, the efficiency of these methods is 0.848, 0.818 and 0.810, respectively. In another study, Bricol et al compared the SVM, ANN, Navy Bays and regression methods for predicting ACS (Berikol, Yildiz, and Özcan 2016). According to the results of this study the prediction accuracy of each of these methods is 99.13%, 99.10%, 88.75%, and 91.26%, respectively.…”
Section: Intracoronary Thrombus Detected On Angiography or Autopsymentioning
confidence: 86%